2011
DOI: 10.3168/jds.2010-3581
|View full text |Cite
|
Sign up to set email alerts
|

Replacing corn with glycerol in diets for transition dairy cows

Abstract: Expansion of the biofuels industry has increased the availability of glycerol as an alternative feed for dairy cows. The objective of this study was to determine the effects of glycerol on feed intake, milk production, rumen volatile fatty acids, and metabolic parameters in transition dairy cows. Multiparous Holstein cows were fed diets containing either high-moisture corn (n=11) or glycerol (n=12) from -28 to +56 d relative to calving. Glycerol was included at 11.5 and 10.8% of the ration dry matter for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
49
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 27 publications
13
49
3
1
Order By: Relevance
“…Furthermore, the purity of the glycerin may also influence its acceptability to the animals. Several previous studies have shown no reduction in dry matter intake for animals fed glycerin (CARVALHO et al, 2011;FARIAS et al, 2012;BARTON et al, 2013). Van Cleef et al (2014), used glycerin with a similar composition to the glycerin used in this study (obtained from biodiesel production from soybeans, comprised of 860 g kg -1 glycerol, 950 g kg -1 water, 60 g kg -1 salts, and less than 0.1 g kg -1 methanol) and found no difference in dry matter intake for feedlot Nelore bulls fed up to 300 g kg -1…”
Section: Intake and Digestibility Of Nutrientsmentioning
confidence: 99%
“…Furthermore, the purity of the glycerin may also influence its acceptability to the animals. Several previous studies have shown no reduction in dry matter intake for animals fed glycerin (CARVALHO et al, 2011;FARIAS et al, 2012;BARTON et al, 2013). Van Cleef et al (2014), used glycerin with a similar composition to the glycerin used in this study (obtained from biodiesel production from soybeans, comprised of 860 g kg -1 glycerol, 950 g kg -1 water, 60 g kg -1 salts, and less than 0.1 g kg -1 methanol) and found no difference in dry matter intake for feedlot Nelore bulls fed up to 300 g kg -1…”
Section: Intake and Digestibility Of Nutrientsmentioning
confidence: 99%
“…One of the explanations why the replacement of sorghum grain by crude glycerol resulted in a reduction (P<0.05) on time spent eating but did have an influence on the DM intake and growth performance is based on the evidence that glycerol increased the molar proportion of propionate at the expense of acetate (Rémond et al 1993;Wang et al 2009;Carvalho et al 2011;Ramos and Kerley 2012;Bartoň et al 2013) or can be directly absorbed by the rumen epithelium (Rémond et al 1993). In both scenarios, crude glycerol can act as a gluconeogenic precursor in the liver and consequently crude glycerol-fed animals in the present study may have been benefited from an enhanced energy status.…”
Section: Resultsmentioning
confidence: 99%
“…Still, there was a tendency to increase milk production in cows supplemented with glycerol during the sixth week of lactation, probably due to changes in metabolism (DeFrain et al 2004). Regarding the composition of milk, no differences were found with the use of up to 13% glycerol (Donkin et al 2009, Osborne et al 2009, Carvalho et al 2011. There was only a subtle reduction in the levels of milk fat and protein within 63 days of early lactation, even when using 1.9% (300 g/d) glycerol in dry matter (Wang et al 2009 b ).…”
Section: ++mentioning
confidence: 93%
“…Some authors have suggested a reduction in food intake using varying levels of glycerol (intervals between approximately 2.7% and 15% dry matter) (DeFrain et al 2004, Donkin et al 2009, Osborne et al 2009, whereas others using similar levels found no such effects on consumption (ranges between 0.6% and 11.5% glycerol in dry matter) (Chung et al 2007, and Swiatkiewicz Koreleski 2009, Carvalho et al 2011. In the production and composition of milk there was greater consensus among authors, since most of them found no deleterious effects on these parameters (Chung et al 2007, Donkin et al 2009, Osborne et al 2009b , Carvalho et al 2011.…”
Section: ++mentioning
confidence: 99%
See 1 more Smart Citation